Adherence to mediterranean diet attenuates the link between impaired fasting glucose and 20-year cumulative incidence of type 2 diabetes: the ATTICA cohort study (2002–2022) - Kechagia, Ioanna; Barkas, Fotios; Liberopoulos, Evangelos; Kaloudi, Polyxeni; Chrysohoou, Christina; Sfikakis, Petros P.; Tsioufis, Costas; Pitsavos, Christos; Panagiotakos, Demosthenes (International journal of food sciences and nutrition, 2025)
The aim of the present study was to evaluate the association between impaired fasting glucose and the 20-year cumulative incidence of type 2 diabetes (T2D), and the role of lifestyle habits, in the ATTICA cohort study (2002-2022). The present analysis was based on 2000 individuals free of T2D at baseline examination (age 43 ± 13 years; 51% women), 773 (39%) had IFG defined by fasting glucose 100-125 mg/dL and HbA1c 5.7-6.4%. Sociodemographic, anthropometric, lifestyle, and clinical parameters were collected at baseline and follow-up examinations. The 20-year cumulative incidence of T2D was 347 out of 773 (45%) participants with IFG. Male sex [RR 1.82, 95%CI (1.36, 2.43)], overweight [RR 6.3, 95%CI (3.7, 10.5)], obesity [RR 5.3, 95%CI (2.5, 11.3)], hypercholesterolaemia [RR 1.71, 95%CI (1.28, 2.28)], smoking [RR 1.67, 95%CI (1.14, 2.44)] and adherence to Mediterranean diet (high vs. low) [RR 0.41, 95%CI (0.26, 0.65)], were significantly associated with the development of T2D in the subjects with IFG, during the 20-year of follow-up. IFG significantly increases the risk of T2D, with male sex, obesity, hypercholesterolaemia, and smoking as key risk factors. Adherence to the Mediterranean diet and weight management were protective, in preventing diabetes progression.